Gestão escolar democrática: a dinâmica de participação do conselho escolar em escolas públicas do ensino fundamental - Guerra, Andreia Tomaz Lima (2023)
The process of redemocratization of the country and the intense debate of academics and education professionals led to the insertion of the principle of democratic school management in public schools in the Federal Constitution of 1988, in the Law of Guidelines and Bases of Education, as well as in state legislation. Among the legal acts created to ensure such a principle is the school board. However, the literature on the subject has shown that there is a misstep between the legislated and the experienced in the daily life of public schools. The effective functioning of the council as a democratic body depends on numerous variables that now facilitate it, and they constrain it. The objective of this dissertation is to analyze how effective the participation of the members of the school boards in the management of public elementary schools in the municipality of Vila Velha/ES. Therefore, a qualitative research was conducted with data collected through semistructured interviews, nonparticipant observation and documentary research in three school boards in the municipality. The analysis was through thematic categorization. The emerging thematic axes made it possible to analyze the environment and the dynamics of the participation of counselors and school boards in the management of these schools. The findings show that there is a diversity of issues dealt with in the council, which suggests greater participation of the school community from its representatives. However, it is perceived greater role of school management within the council, which often circumscribes the participation of the other members in the choice of options already previously defined. Among the members represented in the councils, students are the ones with the least active voice. Among the representatives of the servers, several directors are from outsourced companies, which tends to reduce their engagement in discussions and deliberations. The lack of training and training for counselors negatively influences both the performance of the board members and their perception of their role in school management.